The Science and Technology Labor Force The Value of Doctorate Holders and Development of Professional Careers - Gokhberg, Leonid; Shmatko, Natalia; Auriol, Laudeline (Science, Technology and Innovation Studies, 2016)
This book provides an in-depth analysis of the demand for PhDs on the labor markets of twelve countries. The authors analyze the role of PhDs in the creation of innovation in a knowledge-based economy and examine economic issues such as the return on investment for the education and training of doctoral graduates. To provide a more comprehensive picture of the employment patterns, career paths and mobility of PhDs in selected countries, the book analyzes various data sources such as labor force surveys and censuses. The authors also develop survey approaches and output tables to collect data on the transition from school to work among PhDs. The book will be of interest to policymakers, companies and researchers responsible for research and innovation systems, as well as to doctoral students looking for a professional career outside the academic world.